1968
DOI: 10.1177/004051756803800707
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Degradation of Nylon 66 Filaments

Abstract: Drawn and undrawn nylon 66 filaments were exposed to oxygenated aqueous systems, and the extent of chemical degradation was studied as a function of time. Degradation was estimated by measuring the changes in both chemical and physical properties. At the same time, oxygen absorption measurements were made and these were correlated with the observed structural changes. A significant pH effect on the rate and extent of the degradation was found. Viscosity measurements in m-cresol and other physical and chemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1970
1970
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…35 The weakening of water-absorbed PA66 becomes more severe at elevated temperatures at which the amide groups are decomposed to carboxyl, amine, and imide groups. 36 The change in the molecular structure of PA66 after water adsorption reduces its strength and dimensional stability 3740 and affects its friction and wear effects. Stuart and Briscoe 41 reported that water absorption increased the friction coefficient of PA66 by increasing the contact area.…”
Section: Resultsmentioning
confidence: 99%
“…35 The weakening of water-absorbed PA66 becomes more severe at elevated temperatures at which the amide groups are decomposed to carboxyl, amine, and imide groups. 36 The change in the molecular structure of PA66 after water adsorption reduces its strength and dimensional stability 3740 and affects its friction and wear effects. Stuart and Briscoe 41 reported that water absorption increased the friction coefficient of PA66 by increasing the contact area.…”
Section: Resultsmentioning
confidence: 99%
“…41 The weakening of water-absorbed PA66 becomes more severe at elevated temperatures at which the amide groups are decomposed to carboxyl, amine, and imide groups. 40 The change in the molecular structure of PA66 after water adsorption reduces its strength and dimensional stability 42 46 and affects its friction and wear effects. Stuart and Briscoe 47 reported that water absorption increased the friction coefficient of PA66 by increasing the contact area.…”
Section: Resultsmentioning
confidence: 99%
“…Vachon et al studied oxidative degradation of nylon. 13 In this study the exposure to oxidative aqueous environments was studied in nylon 6-6 filaments. Both chemical and physical properties were studied as a function of exposure.…”
Section: Literature Reviewmentioning
confidence: 99%